Permasalahan Pembelajaran PKN di Sekolah Dasar : Literature Review - Desti Maharani; Adrias Adrias; Fadila Suciana (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This research aims to identify various challenges in teaching Citizenship Education (PKn) in elementary schools and propose solutions to overcome common obstacles in the learning process. The study employs a literature review approach, analyzing various sources such as scholarly articles, journals, and relevant documents. Data collection methods include literature review, listening techniques, and note-taking. The findings indicate several issues in PKn learning at the elementary level, including: (1) teachers’ limited understanding of appropriate learning models aligned with 21st-century education demands, (2) insufficient use of instructional media tailored to students’ characteristics, (3) inadequate supporting facilities such as books and other learning resources, and (4) student learning difficulties influenced by both internal and external factors. This study concludes that implementing innovative learning models, integrating technology into the teaching and learning process, and adopting more flexible and interactive strategies are essential to enhancing the effectiveness of PKn instruction in elementary schools. Moreover, effective communication between teachers, students, and schools plays a crucial role in improving learning quality.